2015
DOI: 10.1002/jsc.2005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Antecedents of Intention to Use Mobile Internet Banking in India: Opportunities for Microfinance Institutions

Abstract: Microfinance institutions in India need to act upon opportunities to extend their reach concentrating their marketing efforts on factors that predict consumers’ intention to use mobile Internet banking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Consumers' perceived integrity of corporations affects their trust (Bryson et al, ; Flavián, Guinalíu, & Torres, ; Fuller, Serva, & Benamati, ). It is mentioned earlier that trust building among the consumers of financial service is crucial since financial crisis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers' perceived integrity of corporations affects their trust (Bryson et al, ; Flavián, Guinalíu, & Torres, ; Fuller, Serva, & Benamati, ). It is mentioned earlier that trust building among the consumers of financial service is crucial since financial crisis.…”
Section: Resultsmentioning
confidence: 99%
“…Prahalad () and Herzog () claimed that a corporation's reputation affects innovation diffusion. Bryson et al () argued that the perceived integrity of a corporation influences adoption. Lieberman () and Mayer, Davis, and Schoorman () found that perceived integrity is an important trust factor, which then influences mobile payment adoption (Zhou, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research has found that the previously unbanked group have the highest expectation of mobile banking and also found the idea most attractive (Shrivastava, 2011). The intention to use mobile banking is based Strategic Change DOI: 10.1002/jsc on the perceived usefulness of the services, attitude toward use of the services, social or 'subjective' norm, and perceived integrity of the banks or other institutions involved (Bryson et al, 2015).…”
mentioning
confidence: 99%
“…Continuous financial innovation requires considering newer technologies, stricter regulation, and increased competition and customers' needs through a participatory approach (Sinha, 2015). Sometimes, an excellent financial performance includes strategies that have a technological component such as mobile banking to increase outreach and reduce costs (Bryson, Atwal, Chaudhuri, & Dave, 2015) or credit scoring to reduce risk (Bumacov, Ashta, & Singh, 2014; Bumacov, Ashta, & Singh, 2017a). Others focus on the social responsibilities of microfinance and either on the social performance or the need to revert to the social mission (Abraham & Kalamkar, 2016).…”
Section: Research Directionsmentioning
confidence: 99%